Preliminary Assessment Of Sediment Transport And Associated Bacteriological Contamination In A Mountainous Rural Karst Area (Sierra De Ubrique, S Spain) - Fernández-Ortega, Jaime; Barberá-Fornell, Juan Antonio; Andreo-Navarro, Bartolomé (My University, 2021)
In rural karst areas, where agricultural and cattle activities are developed and quite often urban waste waters are not properly treated, the high probability of groundwater pollution occurrence together with the high vulnerability of carbonate aquifers poses a potential risk for human health. Sierra de Ubrique is a karstified carbonate aquifer system developed in Jurassic limestones and dolostones located in one of the wettest regions in Spain. This karst aquifer is recharged by rainfall infiltration through karst features, but also from concentrated runoff trough Villaluenga shaft. Groundwater discharge, which is mainly produced through three karst, is also used for drinking water supply of Ubrique town. During flooding conditions, high turbidity events at the two permanent springs are simultaneous to maximum discharge, hindering the exploitation of groundwater for human consumption. This work aims to identify and characterize the main contamination sources and to understand the role of sediment transport in the occurrence of polluted groundwater episodes. For that purpose, a complete climate and groundwater monitoring network has been installed including a weather station and field devices for continuous record of physical‐chemical parameters. Additionally, numerous surface and groundwater sampling campaigns were performed to take samples for chemical and bacteriological determinations. The obtained results allowed the identification of different contamination types of anthropogenic origin as (1) organic (poorly treated waste waters, fecal remains from cattle activity and food factories) and (2) inorganic. The response times in output signals of the two main springs, maximum thresholds of pollutants and statistical correlations among specific chemical/bacteriological‐like parameters lead to explain the main contaminant transport mechanisms, which greatly differ in the examined karst connections.
Keywords: Hidrogeología